A long-lived IL-2 mutein that selectively activates and expands regulatory T cells as a therapy for autoimmune disease. (December 2018) - Peterson, Laurence B.; Bell, Charles J.M.; Howlett, Sarah K.; Pekalski, Marcin L.; Brady, Kevin; Hinton, Heather; Sauter, Denise; Todd, John A.; Umana, Pablo; Ast, Oliver; Waldhauer, Inja; Freimoser-Grundschober, Anne; et al.
Abstract: Susceptibility to multiple autoimmune diseases is associated with common gene polymorphisms influencing IL-2 signaling and Treg function, making Treg -specific expansion by IL-2 a compelling therapeutic approach to treatment. As an in vivo IL-2 half-life enhancer we used a non-targeted, effector-function-silent human IgG1 as a fusion protein. An IL-2 mutein (N88D) with reduced binding to the intermediate affinity IL-2Rβγ receptor was engineered with a stoichiometry of two IL-2N88D molecules per IgG, i.e. IgG-(IL-2N88D)2 . The reduced affinity of IgG-(IL-2N88D)2 for the IL-2Rβγ receptor resulted in a Treg -selective molecule in human whole blood pSTAT5 assays. Treatment of cynomolgus monkeys with single low doses of IgG-(IL-2N88D)2 induced sustained preferential activation of Tregs accompanied by a corresponding 10–14-fold increase in CD4 + and CD8 + CD25 + FOXP3 + Tregs ; conditions that had no effect on CD4 + or CD8 + memory effector T cells. The expanded cynomolgus Tregs had demethylated FOXP3 and CTLA4 epigenetic signatures characteristic of functionally suppressive cells. Humanized mice had similar selective in vivo responses; IgG-(IL-2N88D)2 increased Tregs while wild-type IgG-IL-2 increased NK cells in addition to Tregs . The expanded human Tregs had demethylated FOXP3 and CTLA4 signatures and were immunosuppressive. These results describe a next-generation immunotherapy using a long-lived and Treg -selective IL-2 that activates and expands functional Tregs in vivo . Patients should benefit from restored immune homeostasis in a personalized fashion to the extent that their autoimmune disease condition dictates opening up the possibility for remissions and cures. Highlights: A human IL-2 molecule mutated to decrease binding to the intermediate affinity IL-2 receptor preferentially activates Tregs. Two IL-2 muteins fused to human IgG1 allow for sustained, preferential expansion of Tregs in cynomolgus and humanized mice. As compared to the wild type IL-2 fusion protein, humanized mice expand fewer NK cells in response to the mutein. The dynamic range of Treg increase based on dose suggests the ability to individualize dosing for particular diseases.